Risk and protection factors for self-reported hypertension and diabetes in João Pessoa, Brazil. The VIGITEL survey, 2014. A cross-sectional study - Moreira, Ana Paula Leite; Malta, Deborah Carvalho; Vianna, Rodrigo Pinheiro de Toledo; Moreira, Patrícia Vasconcelos Leitão; Carvalho, Alice Teles de (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: Chronic diseases are the main cause of death among adults and are responsible for most outpatient and hospital care expenses in Brazil. The objective here was to determine the prevalence of hypertension and diabetes and to analyze the associations with risk and protection factors among adults. DESIGN AND LOCAL: Cross-sectional study in a state capital in northeastern Brazil. METHODS: Data on adults of both sexes aged ≥ 45 years who were interviewed in the Vigitel telephone survey in 2014 were analyzed. Prevalence ratios were estimated using Poisson regression, to identify associated factors. RESULTS: Among women, the prevalence of hypertension was 48.4% and of diabetes, 12.7%; among men, the prevalences were 41.9% and 13.8%, respectively. Multivariate analysis showed that for women, age group ≥ 65 years, overweight, self-assessed poor health and dyslipidemia remained associated with higher prevalence of hypertension. For men, overweight and self-assessed poor health remained associated with higher prevalence of hypertension. Regarding diabetes, in the multivariate model for women, age group 55-64 years, schooling level between zero and four years and no regular consumption of beans remained associated with higher prevalence. For men, age groups 55-64 years and ≥ 65 years and being married or in a stable partnership were associated with higher prevalence of diabetes. CONCLUSIONS: The results indicated that the prevalences of hypertension and diabetes were high and that preventable factors were associated with this situation, thus providing support for public policies aimed towards coping with this.